Effect of post-growth annealing on the structural, optical and electrical properties of V2O5 nanorods and its fabrication, characterization of V2O5/p-Si junction diode. (January 2016) - kumar, N. Senthil; Raman, M. Sethu; Chandrasekaran, J.; Priya, R.; Chavali, Murthy; Suresh, R.
Abstract: We report the synthesis of V2 O5 nanorods by utilizing simple wet chemical strategy with ammonia meta vanadate (NH4 VO3 ) and polyethylene glycol (PEG) exploited as precursor and surfactant agent, respectively. The effect of post-annealing on structural, optical and electrical properties of V2 O5 nanorods was characterized by XRD, HRSEM-EDX, TEM, FT-IR, UV (DRS), PL, TG–DTA and DC conductivity studies. The X-ray diffraction analysis revealed that the prepared sample annealed at 150 °C for 5 h which exhibited anorthic phase of V5 O9 and annealed at 300–600 °C showed the anorthic phase change to orthorhombic phase of V2 O5 due to the post-annealing effect. The surface morphology results indicated that increasing temperature caused a change from microrods to a nanorods shape in the morphology of V2 O5 . FT-IR spectrum confirmed that the presence of V2 O5 functional groups and the formation of V–O bond. The optical band gap was found in the range 2.5–2.48 eV and observed to decreases with various annealed temperature. The DC electrical conductivity was studied as a function of temperature which indicated the semiconducting nature. Further, the potential of V2 O5 nanostructures were grown on the p-Si substrate using the nebulizer spray technique. The junction properties of the V2 O5 /p-Si diode were evaluated by measuring current ( I )–voltage ( V ) and AC characteristics.